Prawda i fałsz w humorystycznych opowiadaniach chińskich - Brzozowska, Dorota (Stylistyka, 2019)
The aim of the paper is to explain the differences between the concepts of truth and lie in European and Chinese cultures and to verify if the differences are visible in particular humorous stories. Another objective is to see what the consequences of lying in those stories are, and what they say about the pictured value systems. Pursuing dao was the main task in the scholarship of most of the ancient Chinese philosophers, while the Ancient Greek philosophers considered pursuing truth as their ultimate goal. Dao is a polysemous word in the ancient Chinese language, with multiple meanings of ‘way’, ‘road’, ‘walk’ and ‘speak,’ etc. To check the humorous potential of the Chinese stories, one hundred texts coming from different sources and various time spans have been taken into consideration. Some of them were old and traditional; others came from the pages of the texts for learners of Chinese as a foreign language, and still some other stories were taken from a contemporary anthology. Only five per cent of the stories deal with the subject of truth and lie, and the distribution was not equal in various sources.